Política de cotas e democratização do Ensino Superior: desdobramentos na Universidade Federal do Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
The research “Policy on quotas and democratization of higher education: developments at the Federal University of Amazonas, is the result of an analysis of the contribution of Law 12.711/2012, in the process of democratization of higher education, specifically at the Federal University of Amazonas. Corresponds to a qualitative research based on the historical materialist approach, using the documentary analysis technique arranged in three sections: the first entitled “Education, State and Democracy: Implications in Brazilian Educational Policy”, brings a historical analysis of the unfolding of Brazilian educational policy in a broader and more specific way the higher education policy, with the perspective of identifying which issues were historically linked and how this implied in its constitution, in the case of higher education, in a privilege. We will also analyze how the unfolding of educational policy in Brazil resulted in the black population's access to education being difficult, and in the case of higher education, it became practically inaccessible until the end of the 20th century. The second section, entitled “Between contexts and pretexts: the quota policy” will characterize the quota policy based on the reform of the State and the reform of higher education and the struggle of social movements. Finally, the third section called “Quota Policy in the Amazon Context” highlighted the implementation of the quota policy at federal universities in the Amazon region, in addition to characterizing the implementation of the quota policy at the Federal University of Amazonas. Furthermore, we will outline how the This policy implied the democratization of that University, based on a survey of data related to the student's educational background, ethnic-racial profile and permanence, and the data cataloged in the documents and other sources obtained were grouped and interpreted as part of a movement that contemplates the theoretical and legal support so that we have the establishment of politics on two levels: that of ideality and reality (GARCIA, 2014). As a result, we found that law 12.711 / 2012 enabled a significant increase in access for students from public schools, as well as black, brown and yellow students, allowing for a change in the representativeness of these students in the university scenario, however, it implied a decrease representation of indigenous people. Regarding permanence, the index is relatively average, which indicates the need for institutionalization of permanence policies, which UFAM even adopts several, however with limited reach, which directly affects the issue of democratization. However, this policy was of fundamental importance in the struggle for the democratization of higher education, as it enabled a less unequal dispute in public higher education.
Policy on quotas and democratization of higher education: developments at the Federal University of Amazonas
Keywords: Democratização do ensino; Política educacional brasileira; Negros - Educação; Negros - Educação (Superior); Ensino superior público; CIENCIAS HUMANAS; Democracia; Educação; Políticas educacionais; Política de Cotas; Lei 12.711/2012